2023
DOI: 10.3389/fimmu.2023.1119139
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of necroptosis-related prognostic genes and immune infiltration in idiopathic pulmonary fibrosis

Abstract: BackgroundIPF is an undetermined, progressive lung disease. Necroptosis is a type of programmed apoptosis, which involved in the pathogenesis of lung diseases like COPD and ARDS. However, necroptosis in IPF have not been adequately studied. This study aimed to investigate the necroptosis in IPF and the relationship between necroptosis and immune infiltration, to construct a prognostic prediction model of IPF based on necroptosis-related genes.MethodsGSE110147 was downloaded from the GEO database and utilized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Subsequently, via the selection of ML and WGCNA, a total of 8 significant NRDEGs were identified, including CFLAR, FMR1, GSDMD, IKBKB, MAP3K7, NFKBIA, PTGES3, and SFTPA1. Particularly, several significant NRDEGs have been confirmed that regulated the immune landscape and inflammatory response via necroptosis (Yu et al, 2022;Chen et al, 2023). CFLAR is a crucial regulator in apoptosis, autophagy, and necroptosis [23,392,074].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, via the selection of ML and WGCNA, a total of 8 significant NRDEGs were identified, including CFLAR, FMR1, GSDMD, IKBKB, MAP3K7, NFKBIA, PTGES3, and SFTPA1. Particularly, several significant NRDEGs have been confirmed that regulated the immune landscape and inflammatory response via necroptosis (Yu et al, 2022;Chen et al, 2023). CFLAR is a crucial regulator in apoptosis, autophagy, and necroptosis [23,392,074].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple aberrant pathways interconnect to result in pulmonary fibrosis in a subset of individuals who develop ARDS 44 . Important mediators include the dysregulated release of matrix metalloproteinases during the inflammatory phase of ARDS, which causes epithelial and endothelial injury and unchecked fibroproliferation 45 (Figure 4 A,B).…”
Section: Roles Of Tcs Mediated Cell Communication In Pulmonary Fibros...mentioning
confidence: 99%
“…Apart from apoptosis, necroptosis occurs primarily in alveolar epithelial cells during IPF. 98 RIPK3-based necroptosis in alveolar epithelial cells is involved in IPF via releasing DAMPs. 97 Mechanically, homozygous missense mutations in SFTPA1 trigger Type II alveolar epithelial cell necroptosis during IPF via JNK-based upregulation of RIPK3.…”
Section: Fibrosismentioning
confidence: 99%